Functional capacities of T lymphocyte subsets from synovial fluid and blood in rheumatoid arthritis. Issue 7 (July 1986) - Petersen, J
Abstract : A reverse haemolytic plaque forming cell (PFC) assay was employed to analyse the impact of T suppressor/cytotoxic and T helper cells on B cell function in 10 patients with rheumatoid arthritis (RA). In all cases T8-enriched cells from synovial fluid and blood suppressed the pokeweed mitogen (PWM) induced IgM, IgG, and IgA secretion by autologous lymphocytes to the same degree. The suppression was partly abolished by irradiation of T8-enriched cells. T4-enriched cells from blood increased the PWM induced Ig secretion by autologous blood B cells. In six of 10 patients responses 1.2 to four times higher were obtained with T4-enriched cells from synovial fluid, but in four of 10 patients synovial fluid T4-enriched cells did not increase the PWM responses of blood B cells. T4- and T8-enriched T cells from synovial fluid comprised more Ia+ cells than did T cells from blood (36% v 3% and 43% v 6%). Ia+ T helper and suppressor/cytotoxic cells may modulate in vivo activation of synovial B cells in RA.